Devaluación, balanza comercial y términos del intercambio : Un análisis de equilibrio parcial - Núñez Miñana, Horacio (1967)
In the present paper, the effects of a devaluation on the variables related to the foreign sector of the economy are studied according to the so-called "elasticities approach". Following a precise formulation of the assumptions embodied in the model, the results concerning the quantity of exports and imports, the prices of exportables and importables, the value of exports and imports, the balance of trade (both in domestic and in foreign currencies), and the terms of trade are derived. The LERNER case in which both supply elasticities are assumed infinitely large is studied; it is shown that the MARSHALL-LERNER condition (that the sum of the demand elasticities be greater than unity) becomes a necessary condition for the improvement in the trade balance in this special case, because the terms of trade will suffer the largest deterioration compatible with normal demand and supply elasticities coefficients. Alternative formulae using, on one hand only two elasticities, and on the other hand eight elasticities, are presented in order to complete the analysis. Finally, a brief discussion of the crucial assumptions of the present model is presented.